Impact of fluid injection on fracture reactivation at The Geysers geothermal field. Issue 10 (30th October 2016) - Martínez‐Garzón, Patricia; Kwiatek, Grzegorz; Bohnhoff, Marco; Dresen, Georg
Abstract: We analyze the spatiotemporal distribution of fault geometries from seismicity induced by fluid injection at The Geysers geothermal field. The consistency of these faults with the local stress field is investigated using (1) the fault instability coefficient I comparing the orientation of a fault with the optimal orientation for failure in the assumed stress field and (2) the misfit angle β between slip vectors observed from focal mechanisms and predicted from stress tensor. A statistical approach is applied to calculate the most likely fault instabilities considering the uncertainties from focal mechanisms and stress inversion. We find that faults activated by fluid injection may display a broad range in orientations. About 72% of the analyzed seismicity occurs on faults with favorable orientation for failure with respect to the stress field. However, a number of events are observed either to occur on severely misoriented faults or to slip in a different orientation than predicted from stress field. These events mostly occur during periods of high injection rates and are located in proximity to the injection wells. From the stress inversion, the friction coefficient providing the largest overall instability is μ  = 0.5. About 91% of the events are activated with an estimated excess pore pressure <10 MPa, in agreement with previous models considering the combined effect of thermal and poroelastic stress changes from fluid injection. Furthermore, high seismic activity and largest magnitudes occur on favorably oriented faults with large instability coefficients and low slip misfit angles. Key Points: Faults with low reactivation potential slip at maximum injection pressures A broad range of fault orientations is activated during periods of high injection rates Largest event magnitudes are observed at faults optimally oriented for failure